Failure Diagnosis of Demagnetization in Interior Permanent Magnet Synchronous Motors Using Vibration Characteristics - Takeo Ishikawa; Naoto Igarashi (Applied Sciences, 2019)
The detection of a precursor to the demagnetization of permanent magnets is very important because a high degree of reliability is necessary in permanent magnet synchronous motors (PMSMs). This paper investigated the diagnosis of very slight PM demagnetization. A part of the permanent magnet was altered to non-magnetic material so as to mimic the effect of demagnetization. The vibration characteristics were clarified for low demagnetization in PMSMs driven under vector control by experiments and 3D finite element (FE) analysis. We found that the amplitude of some components of the vibration was approximately proportional to the demagnetization level of the PM and the load torque. Therefore, the measurement of vibration and torque is very useful for the estimation of the magnetization level of PMSMs under vector control except for under very light load.